Financial literacy and digital accounting information systems: Their effect on financial reporting accountability in the Catholic Church - Natasha Maria Angela Pontoh; Agus T. Poputra; Robert Lambey (The Contrarian : Finance, Accounting, and Business Research, 2026)
Accountability in financial reporting is a cornerstone of governance in religious institutions, where congregational trust is increasingly demonstrated through credible and verifiable financial management rather than spiritual leadership alone. Despite the growing adoption of digital accounting information systems, many parishes still experience delays and inconsistencies in financial reporting. This study examines the effect of financial literacy and the Digital Accounting Information System (DAIS) on financial reporting accountability among parish finance officers in the Catholic Church of the Diocese of Manado. Using a quantitative survey design, data were collected from parish finance officers and analyzed through multiple linear regression. The results show that financial literacy and DAIS simultaneously have a significant effect on financial reporting accountability. However, partially, financial literacy does not show a significant effect, whereas DAIS has a strong, positive, and significant effect. These findings introduce the concept of "Faith in Data," in which DAIS functions as a digital bridge of trust and a balancing mechanism that compensates for variations in individual financial literacy. This study contributes to the accounting literature by demonstrating that in a hierarchical pastoral context, digitalization extends beyond administrative efficiency to become a critical instrument of modern governance that ensures systemic reliability and institutional legitimacy.